Single-step resection and reconstruction of orbito-fronto-temporal pathologies using a PMMA CAD-implant - Breuskin, David; Fischer, Gerrit; Oertel, Joachim; Linsler, Stefan (Journal of Neurosurgical Sciences, 2023)
BACKGROUND: Resection of bone infiltrating meningiomas of the sphenoid plane and the orbital walls is a highly challenging neurosurgical procedure. In this study, the authors present 11 cases of fronto-orbital and sphenoid wing meningioma which were subjected to tumor resection and cranioplasty using a pre-designed CAD PMMA-implant in one single staged procedure. METHODS: Eleven cases were prospectively analyzed from January 2011 to December 2018. In all cases preoperative CT scans were performed and evaluated, in order to produce a customized PMMA-implant, fitting the osseous defect left after surgical resection of the predefined tumorous mass. Surgery was performed with standard techniques with the addition of availability of preplanned neuronavigational data as well as a matching template of the implant for intraoperative use. After tumor resection, cranioplasty followed using the predesigned PMMA implant. RESULTS: Gross total resection was achieved in 82% (9 of 11 cases). Mean time of surgery for the combined procedure resulted in 223min±99min, with a mean blood loss of 427±192cc. Mean hospital stay for the combined procedure resulted in 11.5±3 days. In 18% of the cases (2/11), patients suffered from late onset infection of the implant and needed a surgical removal. CONCLUSIONS: The presented data show that gross total resection and subsequent single staged bone reconstruction in osseous sphenoid wing and orbital rim meningiomas can be achieved using predesigned PMMA CAD implants with preplanned tumor resection borders with neuronavigational guidance.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Cranioplasty; Meningioma; Skull base; surgery